UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER BERBANTU MEDIA VIDEO - Kunarto Kunarto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2019)
AbstractTeaching and learning is an educational activity. Educational values color the interactions that occur between teachers and students. But in the learning process that is often used is the lecture method, and the result is student learning motivation is so low that it results in low student learning outcomes. This is evident from the data obtained that from 15 students in Grade IV SD 3 Puyoh Dawe  Kudus only 5 students or 30% of students completed their study. Looking at these problems, researchers are interested in conducting Classroom Action Research with the Application of Media Video Assisted Numbered Heads Together Learning Models. From the research that has been conducted for two cycles by applying Media Video assisted Numbered Heads Together learning models, it can be concluded as follows: (1) Through the application of video media assisted Numbered Heads Together Learning Models can Increase Natural Science Motivation Themes Always Save Energy on Students in Grade IV SD 3 Puyoh Dawe  Kudus 2017/2018 Academic Year become 80%. (2) Through the application of video media assisted Numbered Heads Together Learning Models can Improve Science Learning Results Themes Always Save Energy on Students in Grade IV SD 3 Puyoh Dawe  Kudus 2017/2018 Academic Year at 80% with an average score of 83.3.Keywords: Motivation, Learning Outcomes, NHT assisted video media